Using team building methods with an ice hockey team: An action research case study - Rovio, E.; Arvinen-Barrow, M. M.; Weigand, D. A.; Eskola, J.; Lintunen, T. (The Sport Psychologist, 2012)
Research investigating the use of several team building (TB) interventions collectively in one case study is sparse. The purpose of this study was to evaluate, via action research, the process of implementation of a season-long (12 months) multifaceted TB program with a junior league ice hockey team in Finland. The team consisted of 22 players, aged 15-16 years, and three coaches. Inductive content analyses revealed that performance profiling, individual and group goal setting, and role clarification produced additional value to the TB program. Group norms became a vital part of group goal setting. The results are discussed in relation to existing definitions of TB and the importance of using a multifaceted approach to TB.